The permanence of pregnant workers in unhealthy work environments from the perspective of Direct Action of Unconstitutionality (ADI) 5938/DF: A critical analysis of the labor reform (Research, Society and Development, 2026)
This study critically examines the changes introduced by Law No. 13,467/2017 regarding the possibility of pregnant and breastfeeding workers remaining in unhealthy work environments. The general objective of this study was to examine the constitutional incompatibility of the permanence of pregnant and breastfeeding workers in unhealthy work environments, in light of the protection of the work environment and the principle of the prohibition of social regression. The research adopts a logical-deductive method with a qualitative approach, based on bibliographic, normative, and jurisprudential analysis, with emphasis on the judgment of ADI 5938/DF by the Brazilian Supreme Federal Court. The findings indicate that the labor reform resulted in a social setback by shifting to the worker the burden of proving the harmfulness of the work environment. It is concluded that the Supreme Court's decision reaffirms the centrality of fundamental rights and establishes material limits on legislative action, preventing the flexibilization of essential guarantees for the protection of workers' health.